2020
DOI: 10.1038/s41467-020-14449-z
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced eddy activity in the Beaufort Gyre in response to sea ice loss

Abstract: The Beaufort Gyre freshwater content has increased since the 1990s, potentially stabilizing in recent years. The mechanisms proposed to explain the stabilization involve either mesoscale eddy activity that opposes Ekman pumping or the reduction of Ekman pumping due to reduced sea ice-ocean surface stress. However, the relative importance of these mechanisms is unclear. Here, we present observational estimates of the Beaufort Gyre mechanical energy budget and show that energy dissipation and freshwater content … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
85
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(87 citation statements)
references
References 44 publications
2
85
0
Order By: Relevance
“…In general, the AO will be more dynamic, and because it is also baroclinically unstable, more meso-scale features will be produced (e.g., eddies, meanders, fronts). Consistent with this, the expansion and shift of the Beaufort Gyre (Regan et al, 2019) due to increased freshwater accumulation (+40% since 1970(+40% since , Proshutinsky et al, 2019 is accompanied by an increase in eddy activity (Zhao et al, 2014(Zhao et al, , 2016Armitage et al, 2020) and interruptions of the transpolar drift due to accelerating sea-ice melt (Krumpen et al, 2019). Over 2001Over -2014 Bering Strait volume transport from the Pacific to the AO almost doubled as well (0.7 × 10 6 to 1.2 × 10 6 m 3 s −1 ; Woodgate, 2018).…”
Section: Perspectivesmentioning
confidence: 71%
“…In general, the AO will be more dynamic, and because it is also baroclinically unstable, more meso-scale features will be produced (e.g., eddies, meanders, fronts). Consistent with this, the expansion and shift of the Beaufort Gyre (Regan et al, 2019) due to increased freshwater accumulation (+40% since 1970(+40% since , Proshutinsky et al, 2019 is accompanied by an increase in eddy activity (Zhao et al, 2014(Zhao et al, , 2016Armitage et al, 2020) and interruptions of the transpolar drift due to accelerating sea-ice melt (Krumpen et al, 2019). Over 2001Over -2014 Bering Strait volume transport from the Pacific to the AO almost doubled as well (0.7 × 10 6 to 1.2 × 10 6 m 3 s −1 ; Woodgate, 2018).…”
Section: Perspectivesmentioning
confidence: 71%
“…3) and thinning at the Antarctic Peninsula has triggered speed-up of glaciers upstream (Hogg et al, 2017) as a consequence of reduced ice shelf buttressing. Unlike in Antarctica, where almost all of the ice loss is associated with ice dynamical imbalance, just over half of Greenland's mass loss during this period arose due to increases in meltwater runoff (Enderlin et al, 2014) enhanced by atmospheric circulation during several warm summers (Bevis et al, 2019). The remaining ice loss was due to increased glacier discharge, primarily at Jakobshavn Isbrae (Holland et al, 2008) and at outlet glaciers in the southeast (Howat et al, 2008) and northwest (Moon et al, 2012).…”
Section: Ice Sheetsmentioning
confidence: 99%
“…Grounded ice losses have raised the global mean sea level by 24.9 ± 1.8 and 9.7 ± 2.5 mm in the Northern Hemisphere and Southern Hemisphere respectively, totalling 34.6 ± 3.1 mm over the 24-year period. Although the loss of floating sea ice and ice shelves does not contribute to global sea level rise, sea ice decline increases habitat loss (Rode et al, 2014), coastal erosion (Overeem et al, 2011), and ocean circulation (Armitage et al, 2020) and may affect mid-latitude weather and climate (Blackport et al, 2019;Overland et al, 2016).…”
Section: Earth's Ice Imbalancementioning
confidence: 99%
“…The Arctic sea ice in the Atlantic sector can be predicted from a few years to a decade, because of the strong role exerted by the ocean heat advected from upstream and converged on the position of the sea ice edge (Yeager et al, 2015;Årthun et al, 2017;Dai et al, 2020). Some studies suggested that sea ice persistence in the central Arctic can be modulated by oscillation of the Arctic atmospheric circulation between predominantly cyclonic and anticyclonic circulation regimes over timescales of 5-7 years (Proshutinsky and Johnson, 1997;Armitage et al, 2020). From observations, a remarkable oscillation in SIE and SIV is featuring a pause or enhanced ice loss at a period of 7 years, corresponding to some prominent modes of internal variability, such as the winter North Atlantic Oscillation (NAO, Bitz et al, 1996;Swart et al, 2015;Gascard et al, 2019).…”
Section: Introductionmentioning
confidence: 99%